(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The paper presents the Direct Change Solution (DCS) as a method of intervention in the form of a structured five-phase model aimed at promoting sustainable behavior change. The model is based on psychological theory, autobiographical memory, and neuroscience of behavioral prediction that underline long-term change is not possible through surface-level behavioral changes or motivation. Rather, it is concerned with reorganizing inner psychological mechanisms that are influenced by the previous experiences. The suggested model is composed of five consecutive stages: awareness, recognition, resource identification, new internal decision, and behavioral grounding. These phases allow one to recognize repetitive behavioural patterns, comprehend their adaptive sources, internal strengths and deliberately establish new behavioural reactions. The paper also notes how stabilization processes reaction, choice, and scenario stabilization are effective in cementing these changes over time. The results have indicated that emotional triggers and unaware cognitive systems hold maladaptive patterns and that structural awareness helps individuals to discontinue automatic responses and engage in more adaptive behavior. The study makes a contribution to the field by presenting a systematic and practical model that combines theory with intervention that offers a pathway to permanent transformation of the individual and enhanced psychological functioning.